Recovery of orthographic processing after stroke: A longitudinal fMRI study. (July 2017) - Purcell, Jeremy; Sebastian, Rajani; Leigh, Richard; Jarso, Samson; Davis, Cameron; Posner, Joseph; Wright, Amy; Hillis, Argye E.
Abstract: An intact orthographic processing system is critical for normal reading and spelling. Here we investigate the neural changes associated with impairment and subsequent recovery of the orthographic lexical processing system in an individual with an ischemic left posterior cerebral artery (PCA) stroke. This work describes a longitudinal case study of a patient, whose initials are MMY, with impairments in orthographic lexical processing for reading and spelling at stroke onset, and who recovered these skills within 1 year post stroke. We tested the hypothesis that this acute impairment to reading and spelling would be associated with a selective loss of neural activation in the left fusiform gyrus (FG), and that subsequent recovery would be associated with a gain of neural activation in this region. MMY's case provided a unique opportunity to assess the selectivity of neural changes because she demonstrated a behavioral recovery of naming as well; i.e., if there is neural recovery for reading and spelling, but not naming, then these neural changes are selective to the recovery of orthographic processing. To test our hypothesis, we examined longitudinal behavioral and functional magnetic resonance imaging (fMRI) data of reading, spelling, and visual object naming acquired acutely, 3 weeks, 5 months, and one year post stroke. In confirmation of our hypothesis, the loss and subsequent gain of orthographic lexical processing was associated with up-regulation of neural activation in areas previously associated with orthographic lexical processing: i.e., the left mid-FG and inferior frontal junction (IFJ). Furthermore, these neural changes were found to be selective to orthographic processing, as they were observed for reading and spelling, but not for visual object naming within the left mid-FG. This work shows that left PCA stroke can temporarily and selectively disrupt the orthographic lexical processing system, not only in the posterior region adjacent to the stroke, but also in relatively distant frontal orthographic processing regions.